AGILE MANUFACTURING THROUGH INVENTORY MANAGEMENT - Sudirga, Rudy Santosa; Nurprihatin, Filscha; Rembulan, Glisina Dwinoor; Yuniarto, Yustinus (Jurnal Pengabdian dan Kewirausahaan, 2021)
Inventory management is a systematic approach to sourcing, storing, and selling inventory both raw materials (components) and finished goods (products). In business terms, inventory management means the right stock, at the right levels, in the right place, at the right time, and at the right cost as well as price. Inventory management refers to the process of ordering, storing and using a company's inventory. This includes the management of raw materials, components and finished products, as well as warehousing and processing such items. For companies with complex supply chains and manufacturing processes, balancing the risks of inventory gluts and shortages is especially difficult. At the same time, inventory can be thought of as a liability (if not in an accounting sense). A large inventory carries the risk of spoilage, theft, damage or shifts in demand. Inventory must be insured, and if it is not sold in time it may have to be disposed of at clearance prices or simply destroyed. For these reasons, inventory management is important for businesses of any size. Knowing when to restock inventory, what amounts to purchase or produce, what price to pay as well as when to sell and at what pric can easily become complex decisions. Small businesses will often keep track of stock manually and determine the reorder points and quantities using Excel formulas. Larger businesses will use specialized enterprise resource planning (ERP) software.